Chemoimmunotherapy for cutaneous melanoma with dacarbazine and epifocal contact sensitizers: results of a nationwide survey of the German Dermatologic Co-operative Oncology Group - Terheyden, Patrick; Schadendorf, Dirk (Journal of cancer research and clinical oncology, 2007)
Purpose: To scrutinize published data from small mono-centric studies and case reports which implicated high response rates and promising survival times for a combination therapy consisting of epifocal dinitrochlorobenzene (DNCB) and dacarbazine (DTIC) for metastasized melanoma. This therapy merges the effects of an allergic contact dermatitis elicited at the site of a cutaneous metastasis, and systemic chemotherapy. Methods: We performed a retrospective survey with nine German centers and evaluated 72 patients treated from 1993 to 2005. Results: The objective response rate in stage III melanoma (n = 39) was 62%. In contrast, only 9% objective responses were observed in 33 stage IV patients. Interestingly, more than half of patients with objective remissions remained progression-free for more than 1 year irrespective of the stage of disease. Conclusions: Epifocal DNCB combined with DTIC is effective in patients with regionally metastasized melanoma not amenable to surgery or isolated limb perfusion, whereas in stage IV disease in spite of few durable remissions the addition of DNCB does not improve the therapeutic efficacy of DTIC.
Gesehen am 05.02.2021